Comparison of radiation levels from computed tomography and conventional dental radiographs - Ngan Daniel C.S; Kharbanda Om P.; Geenty Joseph P.; Ali Darendeliler M. (Sciendo, 2003)
Background: With the increasing use of computed tomography (CT) in oral diagnosis and treatment planning, concern has been expressed about the high levels of radiation used, and the associated risks.